Educational interventions to promote self-regulated learning in vocational schools - a systematic review - Mejeh, Mathias [Verfasser]; Grieder, Corinne [Verfasser] (My University, 2025)
„In the evolving landscape of the 21st century, characterized by dynamic global challenges such as health crises, climate change, and rapid technological advancements, the imperative of lifelong learning has become more pronounced than ever. Self-Regulated Learning (SRL) plays a pivotal role in lifelong learning, involving independent, self-directed behaviors to enhance knowledge and skills. While the significance of SRL is widely acknowledged in the broader context of lifelong learning, its specific role in vocational schools is a critical aspect that requires careful investigation. In these specialized educational settings, effective SRL practices are not only integral to individual academic success but are also crucial for fostering the competencies essential for a thriving professional career. However, there is a need for a systematic analysis of how SRL is fostered within vocational schools. Despite its importance, the current best practices for promoting successful SRL in vocational schools remain underexplored. Therefore, this study aimed to systematically review intervention studies focused on changing educational practices related to SRL in vocational schools. Specifically, we addressed two key research questions: (1) What are the characteristics of intervention studies aimed at fostering SRL in vocational schools? and (2) What is the quality of these interventions in terms of their impact on promoting SRL?“ (authors‘ abstract; BIBB-Doku)
Keywords: P 2.3 Auszubildende; L 2.1 Lernformen; L 3 Lehr-Lern-Forschung; 370; Beurfsschule; Berufsschüler; Lernform; Selbstgesteuertes Lernen; Lehr-Lern-Forschung; Literaturanalyse; Learning Analytics